An Overview of Side Effects on Post-Placental IUD Acceptors by Independent Practice Midwives in Jembrana Regency - Wati, Ni Putu Eka Yadnya; Darmayasa, I Made (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: Women who have given birth three or more times will be advised to use the Long-Acting Reversible Contraceptives (LARCs) to avoid the risk of complications in both mother and baby. One of the most widely used LARCs is the Intrauterine Device (IUD); however, the use of IUDs in Indonesia is recorded low. IUD acceptors in Couples of Childbearing Age in Indonesia in 2022 were still very low, i.e., 7.7% of the total 27.3 million couples, while data in Bali Province in 2022 showed the number of IUD users with a percentage of 32.3% of the total 777,016 couples; while in Jembrana Regency, it was 23.6% of the total 48,471 couples. The insertion of a post-placental IUD is one of the opportunities to prevent unplanned or unwanted pregnancies. This research was conducted to get an overview of side effects on Post-placental IUD acceptors conducted by Independent Practice Midwives in Jembrana Regency. Methods: This study uses descriptive research describing post-placental IUD acceptors by independent practice midwives. The samples include 75 data obtained from the delivery register of Independent Practice Midwives in Jembrana Regency who served postpartum IUDs from January 2021 to November 2024. Results: The characteristics of post-placental IUD acceptors are 76% at the age group of 20-35 years and 77.3% working mothers or taking care of the household. Moreover, 78.7% completed secondary education, 62.7% have more than one child, and 60% have used IUDs for more than 1 year. IUDs were reported to cause long period of menstruation (13.3% of respondents), cause abdominal pain (9.3% of respondents), have respondents to replace IUDs with other contraceptive methods (8% of respondents), and experience expulsion. Conclusion: Post-placental IUD insertion by Independent Practice Midwives in Jembrana Regency is effective resulting in low side effects, expulsion, and failure.Gambaran Eefek Samping Pada Akaseptor IUD Pasca-Plasenta oleh Bidan Praktek Mandiri di Kabupaten JembranaAbstrakTujuan: Ibu yang melahiran tiga kali atau lebih akan disarankan menggunakan Metode Kontrasepsi Jangka Panjang (MKJP) karena berisiko mengalami komplikasi baik pada ibu maupun bayi. Salah satu MKJP yang banyak digunakan adalah Intra Uterine Device (IUD). Namun, pengguna IUD secara nasional masih rendah. Akseptor IUD pada pasangan usia subur (PUS) di Indonesia tahun 2022 masih sangat rendah yaitu 7,7% dari total 27.3 juta PUS, sedangkan data di Provinsi Bali tahun 2022 menunjukkan jumlah pengguna IUD dengan persentase 32,3% dari total 777.016 jumlah Pasangan Usia Subur (PUS), dan di Kabupaten Jembrana 23,6% dari total 48.471 jumlah PUS. Pemasangan IUD pasca-plasenta menjadi salah satu kesempatan untuk mencegah terjadinya kehamilan yang tidak direncanakan atau dikehendaki. Penelitian ini dilakukan agar mendapat gambaran efek samping pada akseptor IUD pasca-plasenta yang dilakukan oleh Bidan Praktik Mandiri di Kabupaten Jembrana.Metode: Penelitian ini merupakan penelitian deskriptif dari data akseptor IUD pasca-plasenta yang dipasang oleh Bidan Praktik Mandiri (BPM). Sampel yang digunakan adalah 75 sampel dengan data didapatkan dari register persalinan Bidan Praktik Mandiri di Kabupaten Jembrana yang melayani IUD pascasalin rentang Januari 2021-November 2024.Hasil: Karakteristik akseptor IUD pasca-plasenta didapatkan menurut usia 76% merupakan wanita usia subur kelompok usia 20 - 35 tahun, dan 77,3 % sebagai ibu bekerja mengurus rumah tangga. Sebanyak 78,7% menyelesaikan pendidikan paling banyak adalah level menengah, menurut jumlah anak 62.7% merupakan multipara, dan 60% telah memakai IUD lebih dari 1 tahun. Efek samping penggunaan IUD dilaporkan haid yang lama, yaitu sebanyak 13.3 % responden dan nyeri perut sebesar 9.3% responden. Sedangkan kegagalan IUD menyebabkan 8% responden mengganti IUD dengan metode kontrasepsi lain dan 1.3% responden mengalami ekspulsi.Kesimpulan: Pemasangan IUD pasca-plasenta oleh Bidan Praktik Mandiri di Kabupaten Jembrana efektif dengan efek samping, ekspulsi, dan kegagalan yang rendah.Kata kunci: efek samping, IUD pasca-plasenta, kegagalan